ANALISIS WILLINGNESS TO PAY PENGGUNA JASA BUS RAPID TRANSIT (BRT) BANJARBAKULA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Nadya Dwi Yuniarty; Khairi Pahlevi (PPJP Universitas Lambung Mangkurat, 2020)
This study aims to: (1) analyze the willingness to pay (WTP) users of Banjarbakula Bus Rapid Transit (BRT) services (2) determine the effect of education, income, and number of family members on the WTP value of Bus Rapid Transit (BRT) respondents Banjarbakula.This type of research is quantitative research with the method used that is using the Stated Preference method and multiple linear regression analysis. The variables used are education, income, and number of family members. The data used are primary data taken from the source, namely Banjarbakula BRT users and the Transportation Office of South Kalimantan Province.The results showed the average willingness to pay respondents amounted to Rp 5,720. If there is an increase in quality, the average willingness to pay the respondent becomes Rp10,180. The factors of education, income and number of family members together affect the WTP value of users of Banjarbakula BRT services.Keywords: Education, Income, Number of Family Members, WTP BRT Banjarbakula